MENINGKATKAN KEMANDIRIAN ANAK USIA DINI MELALUI METODE PEMBELAJARAN MONTESSORI - Rohmah, Pia Sani Sadiatu; Aprianti, Ema (IKIP Siliwangi, 2021)
Writing this article aims to determine how to increase children's independence through the Montessori learning method. This article uses the literature study method for initial preparation in developing a research framework in obtaining data in the field. The data collection technique uses the documentation method on the results of research and published papers. Data analysis using bibliographic annotations. The sample in this study is a study entitled